Financial Ecological Environment, Financing Constraints, and Green Innovation of Manufacturing Enterprises: Empirical Evidence From China - Zhao, Linhai; Wang, Yajun (Frontiers in Environmental Science, 2022)
In the context of carbon neutrality strategy, how to facilitate green innovation of enterprises and promote industrial upgrading has become a key issue. We explore the relationship between financial ecological environment, financing constraints and green innovation of manufacturing enterprises based on endogenous growth theory and stakeholder theory. Manufacturing companies listed in Shanghai Stock Exchange and Shenzhen Stock Exchange from 2010 to 2020 are taken as samples. With the help of principal component analysis, a comprehensive index of financial ecological environment on yearly basis is constructed. SA index is employed to measure financing constraints of firms, and the number of granted green patents is used to measure the green innovation of manufacturing enterprises. The conclusion indicates that the green innovation of manufacturing enterprises will relax their financing constraints, the financial ecological environment positively moderates the relationship between green innovation and corporate financing constraints, and a good financial ecological environment will enhance the mitigation effect of green innovation of manufacturing enterprises on their financing constraints. Policy implications are given according to the conclusion.